2010
DOI: 10.1093/jjco/hyp184
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Values of Tau and ERCC1 in Advanced Breast Cancer Patients Treated with Paclitaxel and Cisplatin

Abstract: Tau expression but not excision repair cross-complementing 1 in advanced breast cancer predicts poor response to combination chemotherapy of paclitaxel and cisplatin. However, tau expression is significantly associated with longer overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
2
24
2
Order By: Relevance
“…However, this study is now the second cohort to fail to show an association between MAP-tau expression levels and response to taxane therapy in the metastatic setting. Although both studies [15] are relatively small, the lack of association in either case raises question regarding the value of measuring MAP-tau in large taxane trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study is now the second cohort to fail to show an association between MAP-tau expression levels and response to taxane therapy in the metastatic setting. Although both studies [15] are relatively small, the lack of association in either case raises question regarding the value of measuring MAP-tau in large taxane trials.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced breast cancer patients, an early study of MAP-tau expression found no prediction of benefit from taxane therapy [13]. However, two additional studies of advanced breast cancer patients found high MAP-tau expression predictive for response to paclitaxel [14,15] and a positive prognostic marker for improved overall survival [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Microtubule associated protein (MAP) Tau binds to β-tubulin in the same place as paclitaxel and may consequently compete with this drug (15). Some studies focused on breast and gastric cancer revealed that patients with low expression of Tau protein benefit from paclitaxel therapy (16)(17)(18)(19)(20). Nevertheless, other studies, based on larger groups of breast cancer patients did not confirm these results (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Sixty percent of Tau-negative expression showed favorable response (CR or partial response [PR]) to paclitaxel administration compared to 15% of Tau-positive expression. Shao et al14 analyzed Tau expression in 54 advanced breast cancer patients who received first-line chemotherapy of paclitaxel and cisplatin. Tau expression was significantly associated with lower overall response rate (CR or PR) (p=.02).…”
Section: Discussionmentioning
confidence: 99%